Physical Training Profile and Training Patterns of Paragliding Athletes - Carolin Purba; Aam Ali Rahman; Ayi Suherman (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to determine the ideal physical training program and optimal training patterns for paragliding athletes. The research method used is qualitative with a case study approach to describe and analyze the perceptions of athletes and coaches. In this case, the participants in this study were 1 female athlete aged 22 years and 1 male coach aged 61 years in the paragliding sport of DKI Jakarta. Questionnaires, interviews, and documentation were used to collect data. The results of the athlete's questionnaire with the following indicators: 1) talent/seed guidance 83%, 2) coaching 67%, 3) physical, technical, tactical and psychological training program 75%, 4) nutrition intake 100%, 5) training cycle 50%, 6) facilities and infrastructure 100%, 7) Achievement 100%. Likewise, the results of the coach's questionnaire with the following indicators: 1) talent/seed guidance 100%, 2) coaching program 100%, 3) training cycle 75%, 4) management structure 80%, 5) facilities and infrastructure 50%, 6) Achievement 100%. This study shows that the ideal physical training pattern for paragliding athletes is one that is systematic, progressive, and tailored to the needs of the athlete, the optimal training pattern to improve the performance of paragliding athletes is to follow a structured and consistent training pattern.